Accompaniment in Creating Web-Based Learning Material Resources for English Teachers - Sumarsih (ALTSA Publisher, 2021)
The objective of this paper is to describe on how to assist the English Teachers in creating web-based learning material. There are three main steps in this community service project; preparation, implementation and evaluation. The recipients of this community service project were English teachers in Siabu District, from Primary School teachers, First Level Secondary School teachers, to Upper Secondary School teachers who were officially invited through the Head of Education of Siabu District. From this community service activities, activist found that this community service activity has a positive impact on the progress of education in the district of Siabu and also to the State of Indonesia globally. Therefore, this kind of project is suggested to be implemented in many areas in Indonesia.